Georgian Territories in the System of State Administration of the Russian Empire, 1801–1812: the Search for an Optimal Model - Urushadze, A. T. (Гуманитарные и юридические исследования, 2024)
Introduction. The article is devoted to the analysis of the process of administrative and political integration of Georgian territories into the Russian Empire. The chronological period under consideration (1801-1812) covers the time from the entry into the Russian state of Eastern Georgia (Kartli-Kakheti) to the Kakhetian Uprising of 1812. Materials and Methods. The article is based on a wide range of published historical sources. Theoretically, the study is based on the analysis of the impact of regional political events and conditions on determining the government course. Analysis. The article analyzes various administrative models that were used by the Russian government in the process of integrating Georgian lands at this stage. Eastern Georgia became part of the Russian Empire as the Georgian Province. The article shows that the management system of this region can be considered a cooperative management model, which is characterized by the interaction of various political regimes under the general control of the imperial metropolis. West Georgian territories in the early nineteenth century. They were part of Russia with the rights of broad administrative autonomy, which corresponds to an indirect management model. The transition to a model of indirect governance in Eastern Georgia was also discussed when choosing a government course on the southern outskirts of the empire. The Kakheti uprising of 1812 became not only one of the largest crises of the Russian administration, but also an important point in the search for an administrative and political optimum in the region. Subsequent projects for the integration of Georgian territories no longer considered indirect governance as a possible alternative. Results. The result of the troubles and problems in the organization of governance in the Georgian territories was the formation by the imperial elite of ideas about a single political and legal space as an imperative of state construction. This will become especially noticeable already in the reign of Nicholas I.